FRAMING MEDIA DAN PENISTAAN AGAMA : STUDI KASUS TAJUK RENCANA HARIAN REPUBLIKA DAN KOMPAS Media Framing And Religious Blasphemy: A Study On Editorial (Tajuk Rencana) In Republika And Kompas Daily Newspaper - Novi Maria Ulfah (Balai Penelitian dan Pengembangan Agama Semarang, 2017)
The case of alleged religious blasphemy committed by the Jakarta Governor, Basuki Cahaya Purnama alias Ahok attracted a great deal of public attention. Almost all mass media reported the progress of the case in different ways. This study is intended to know how the framing of Republika and Kompas newspapers towards religious blasphemy case in the first round on February 15, 2017. The method used in this study is library research. Data taken from media is editorial columns (Tajuk Rencana) during February or during campaigns from Republika and Kompas newspapers. Kompas wrote three editorials in its headline: Stop Politik Uang, KTP Palsu Jelang Pilkada and Tetap Menjaga Masa Tenang. While Republika wrote 5 editorials: Menjaga Pilkada Damai, Tetap Tenang Jangan Terprovokasi, Tanggung Jawab Bersama, Jaga Kedamaian Aksi 112, Mengawal Suara Bersama-Sama. The text data from that media is then analyzed by framing analysis. The findings show that Kompas tends to be more neutral in the title and diction preferences than Republika which tends to take on mainly Muslims side.